Could lymphadenectomy be avoided in locally advanced cervical cancer patients administered preoperative chemoradiation? A large-scale retrospective study. Issue 12 (December 2017) - Ferrandina, Gabriella; Distefano, Mariagrazia; Mascilini, Floriana; Gallotta, Valerio; Chiantera, Vito; Cosentino, Francesco; Costantini, Barbara; Ercoli, Alfredo; Pedone Anchora, Luigi; Fanfani, Francesco; Margariti, Alessandro Pasquale; Valentini, Vincenzo; et al.
Abstract: Introduction: To identify a subset of cervical cancer (CC) patients administered chemoradiation (CT/RT) plus radical surgery (RS), who can be spared lymphadenectomy, and complications. Patients and methods: 430 Stage IB2-IIB patients without LN involvement at imaging were accrued (March 1996–December 2015) at Gynecologic Oncology Unit of the Catholic University of Rome/Campobasso. CT/RT consisted of pelvic irradiation plus cisplatin based chemotherapy. Objective response was evaluated according to RECIST criteria; radical hysterectomy and pelvic ± aortic lymphadenectomy was attempted in patients achieving response or stable disease. Surgical morbidity was classified according to the Chassagne grading system. Results: 421 cases underwent RS; metastatic pelvic and aortic LNs were documented in 10.7%, and 8.8% of cases, respectively. In patients without residual tumor in the cervix, there was only 1 case (0.53%) with positive pelvic LNs, and 1 case (2.3%) with metastatic aortic LNs. Analysis of patients according to pre- and post-CT/RT imaging was able to select cases without any metastatic LNs: in patients with negative pelvic LNs at pre- and post-CT/RT imaging, none of cases without residual disease in the cervix had metastatic pelvic or aortic LNs. Of 149 early complications, 76 (51.0%) were lymphovascular. The most frequent late complications were lymphovascular (N = 25/61, 41.0%). Conclusion: Lymphadenectomy could be avoided in stage IB2-IIB CC patients undergoing preoperative CT/RT, when a careful evaluation of pre- and post-CT/RT imaging and histological assessment of no residual disease in the cervix is made. This approach may avoid lymphadenectomy in 40% of patients with a favourable impact on lymphovascular morbidity.